2022
DOI: 10.1111/myc.13471
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence and subgroup analyses of coronavirus disease (COVID‐19) associated Candida auris infections (CACa): A systematic review and meta‐analysis

Abstract: Background Increased hospitalisation rates in the Coronavirus disease 19 (COVID‐19) era lead to a new wave of hospital‐acquired infections such as emerging multidrug‐resistant Candida auris. We aimed to evaluate and estimate the global prevalence of coronavirus‐associated C. auris infection (CACa). Methods We searched related databases between December 2019 and April 2022 for studies that reported data about CACa. Meta‐analysis was performed using MedCalc software version 20.104 according to the DerSimonian an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 86 publications
0
35
0
Order By: Relevance
“…COVID-19 as a risk factor for invasive candidiasis has only recently emerged. A meta-analysis looking at COVID-19-associated candidiasis (CAC) found that the pooled prevalence of resistant NAC, specifically Candida auris, was 5.7% but with a mortality as high as 67% [25]. CAC can be due to two major groups of risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 as a risk factor for invasive candidiasis has only recently emerged. A meta-analysis looking at COVID-19-associated candidiasis (CAC) found that the pooled prevalence of resistant NAC, specifically Candida auris, was 5.7% but with a mortality as high as 67% [25]. CAC can be due to two major groups of risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the health consequences of COVID-19 with IFIs superinfection have not been well understood. In resource-poor settings, COVID-19 patients are at a high risk of developing candidosis, Pneumocytis pneumonia, mould infection/pulmonary aspergillosis, and mucormycosis [ 12 , 13 ]. This risk is significantly associated with prolonged use of mechanical ventilator, underlying diabetic conditions, corticosteroid use, and damage to pulmonary epithelial cells due to severe influenza [ 10 , 11 ].…”
Section: Africa: Current Statisticsmentioning
confidence: 99%
“…In recent years, outbreaks of C. auris have been reported in a variety of countries, including the USA, 4 UK, 5 India, 6 South Korea, 7 Europe 8 and recently in Lebanon 9 . In addition, several outbreaks of C. auris have been reported worldwide since the emergence of coronavirus disease 2019 (COVID‐19) in December 2019 9–12 . Phylogenetic analyses of C. auris isolates from around the world revealed five distinct clades.…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, several outbreaks of C. auris have been reported worldwide since the emergence of coronavirus disease 2019 (COVID- 19) in December 2019. [9][10][11][12] Phylogenetic analyses of C. auris isolates from around the world revealed five distinct clades. These include clade I (South Asian), clade II (East Asian), clade III (South African), clade IV (South American) and the recently identified clade V (potential Iranian clade).…”
Section: Introductionmentioning
confidence: 99%